Fabrication of nanoporous gold thin films on silicon substrate by multilayer deposition of Au and Ag - Kim, Minho; Ha, Woo-Jin; Anh, Jin-Woo; Kim, Hye-Sung; Park, Sang-Whan; Lee, Dongyun (ELSEVIER SCIENCE SA, 2009)
Nanoporous gold thin films were fabricated on Si substrates by dealloying Au-Ag alloy films, created by elevated temperature annealing of deposited Au and Ag multilayers. The effects of various chemical compositions, heat treatment, and dealloying methods and conditions (dissolution rate) were examined. Nanoporous gold films showing significantly less cracking in tens of millimeters and reduced ligament size under 10 nm were fabricated from properly alloyed Au-Ag films using a well-controlled electrochemical dealloying process with diluted aqueous HClO4 as an electrolyte. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: SURFACES; METALS